An Interplay of Cooperativity between Cation⋅⋅⋅π, Anion⋅⋅⋅π and CH⋅⋅⋅Anion Interactions. Issue 6 (19th March 2013) - Mandal, Tarun K.; Samanta, Siddhartha; Chakraborty, Sourav; Datta, Ayan
Abstract Mixed cation (Li+, Na+ and K+) and anion (F−, Cl−, Br−) complexes of the aromatic π‐surfaces (top and bottom) are studied by using dispersion‐corrected density functional theory. The selectivity of the aromatic surface to interact with a cation or an anion can be tuned and even reversed by the electron‐donating/electron‐accepting nature of the side groups. The presence of a methyl group in the OCH3, SCH3, OC2H5 in the side groups of the aromatic ring leads to further cooperative stabilization of the otherwise unstable/weakly stable anion⋅⋅⋅π complexes by bending of the side groups towards the anion to facilitate CH⋅⋅⋅anion interactions. The cooperativity among the interactions is found to be as large as 100 kcal mol−1 quantified by dissection of the three individual forces from the total interaction energy. The crystal structures of the fluoride binding tripodal and hexapodal ligands provide experimental evidence for such cooperative interactions.